IL-4 mRNA Is Downregulated in the Liver of Pancreatic Cancer Patients Suffering from Cachexia. (2nd January 2017) - Prokopchuk, Olga; Steinacker, Jürgen M.; Nitsche, Ulrich; Otto, Stephanie; Bachmann, Jeannine; Schubert, Elaine C.; Friess, Helmut; Martignoni, Marc E.
ABSTRACT: Background. Interleukin-4 (IL-4) together with interleukin-13 (IL-13) play an important role in inflammation and wound repair, and are known to be upregulated in human skeletal muscle after strenuous physical exercise. Additionally, these cytokines may act as autocrine growth factors in pancreatic cancer cells. We hypothesize that IL-4, IL-13, and their corresponding receptors are involved in mechanism of cancer cachexia. Methods. Tissue samples from human skeletal muscle, white fat, liver, healthy pancreas, and pancreatic ductal adenocarcinoma were analyzed by quantitative real-time polymerase chain reaction for mRNA expression levels of IL-4, IL-13, IL-4 receptor α, and IL-13 receptor α1. Results. We demonstrate for the first time that liver IL-4 mRNA is downregulated in vivo in patients with pancreatic cancer and cachexia. Additionally, IL-4 mRNA in the liver inversely correlated with musculus psoas thickness. Conclusion. We speculate that suppression of IL-4 is involved in cancer cachexia, although the exact mechanisms have to be further elucidated.